إضافة الصفة إلى الموصوف في القرآن الكريم دراسة في التركيب والدلالة والسياق (Journal of the College of Basic Education, 2022)
This research seeks to study one of the clear methods, in the Holy Quran, which is the addition of the attribute to the prescribed, and the implications of this method on the characteristics of the rhetoric and rhetoric.It will appear that the addition of the characteristic to the prescribed involves several methodological advantages, namely verbal relaxation, exaggeration, artistic image drawing, and broadening of the possibilities of expression.